KERAGAAN AGROINDUSTRI KERIPIK SINGKONG DI KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Lea Ayu Utari; Fembriarti Erry Prasmatiwi; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The purposes of this research were to analyze the performance of cassava chips agroindustry reviewed from procurement of raw materials, labor productivity, production capacity, product quality, delivery speed, flexibility, and added value and income.  The research used was a survey method.   Research data collection was carried out in March 2019 in Gedong Tataan Subdistrict with the consideration that agro-industries were actively producing continuously and had the potency to be developed.  The research locations were in three villages of cassava chips agro-industry centers, namely Karang Anyar Village, Bagelen Village, and Sungai Langka Village.  Respondents were 14 cassava chips agro-industries.  Raw material procurement, product quality, delivery speed, and flexibility were analyzed qualitatively descriptively.  Productivity, production capacity, and income were analyzed quantitatively.  Added value is analyzed using the Hayami method.  The results showed that the procurement of raw cassava chips was correct in the type and quantity, while it was not correct in place.  The average of productivity per month was 41.65 kg / HOK and the average of production capacity per month was 79%.  Product quality and delivery speed were good enough, and flexibility was not optimal.  The agroindustry had a positive added value, profit with R/C>1, and the average of income per month of IDR 7,613,146.29.Key words: agroindustry, cassava chips, performance